DHHC5 facilitates oligodendrocyte development by palmitoylating and activating STAT3. Issue 2 (1st November 2021) - Ma, Yanchen; Liu, Huiqing; Ou, Zhimin; Qi, Chen; Xing, Rui; Wang, Shiyun; Han, Yinuo; Zhao, Tong‐Jin; Chen, Ying
Abstract: Myelin sheath is an important structure to maintain functions of the nerves in central nervous system. Protein palmitoylation has been established as a sorting determinant for the transport of myelin‐forming proteins to the myelin membrane, however, its function in the regulation of oligodendrocyte development remains unknown. Here, we show that an Asp‐His‐His‐Cys (DHHC) motif‐containing palmitoyl acyltransferases, DHHC5, is involved in the control of oligodendrocyte development. Loss of Zdhhc5 in oligodendrocytes inhibits myelination and remyelination by reducing total myelinating oligodendrocyte population. STAT3 is the primary substrate for DHHC5 palmitoylation in oligodendrocytes. Zdhhc5 ablation reduces STAT3 palmitoylation and suppresses STAT3 phosphorylation and activation. As a result, the transcription of the myelin‐related and anti‐apoptosis genes is inhibited, leading to suppressed oligodendrocyte development and myelination. Our findings demonstrate a key role DHHC5 in controlling myelinogenesis. MAIN POINTS: DHHC5 regulates oligodendrocyte development by palmitoylating STAT3.